PENGARUH LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PERUSAHAAN LQ 45 YANG TERDAFTAR DI BEI PERIODE 2016-2020) - Pramita, Risky Yunas Restu; Wahyuni, Ika; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
LQ45 is a type of index used to measure the price performance of stocks that have high liquidity and large market capitalization and are supported by good company fundamentals. There are 45 preferred stocks in the LQ45 stock index which are selected every 6 months. The stocks that occupy the LQ45 index are stocks that have high liquidity and market capitalization from the total number of shares on the IDX. This study aims to test whether liquidity has an effect on dividend policy by using profitability as an intervening variable. The sample in this study is LQ 45 companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period, as many as 30 companies. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation-Partial Least Square (PLS-SEM) method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Liquidity has a positive but significant effect on Profitability, Liquidity has a positive but not significant effect on Dividend Policy, Profitability has a positive but significant effect on Dividend Policy, Liquidity has a positive and significant effect on Dividend Policy through Profitability.